2012
DOI: 10.1111/j.1365-2923.2012.04272.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of expertise in mental health service provision for lesbian, gay, bisexual and transgender communities

Abstract: Data from this study suggest there are few opportunities for medical providers to access training and gain expertise in the provision of care to LGBT people. Additional research is needed to consider whether the lack of LGBT health content in medical and psychiatric training programme curricula indirectly contributes to the health disparities experienced by these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 25 publications
2
76
0
1
Order By: Relevance
“…A Canadian study documented that opportunities for LGBT-related health training are inadequate for mental health professionals; it cited the lack of training as a significant challenge to meeting LBGT mental health needs. 18 A 1998 study of 92 US family medicine department predoctoral chairs found that most departments reported zero hours spent teaching about LGB-related issues. 19 A 2011 survey of 132 US medical schools' deans revealed that a median of 5 preclinical and clinical hours were dedicated to LGBT-related topics; many institutions reported having zero hours of training.…”
mentioning
confidence: 98%
“…A Canadian study documented that opportunities for LGBT-related health training are inadequate for mental health professionals; it cited the lack of training as a significant challenge to meeting LBGT mental health needs. 18 A 1998 study of 92 US family medicine department predoctoral chairs found that most departments reported zero hours spent teaching about LGB-related issues. 19 A 2011 survey of 132 US medical schools' deans revealed that a median of 5 preclinical and clinical hours were dedicated to LGBT-related topics; many institutions reported having zero hours of training.…”
mentioning
confidence: 98%
“…Discrimination, homophobia, and lack of attention regarding gender neutral language have been observed [10, 11]. Recommendations for different medical contexts like primary care, mental health, oncology, and public health are available [4, 1216]. However, there is still a lack of training resources [16], and the special needs of LGBT (Lesbian, Gay, Bisexual, Transgender) patients are neglected worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations for different medical contexts like primary care, mental health, oncology, and public health are available [4, 1216]. However, there is still a lack of training resources [16], and the special needs of LGBT (Lesbian, Gay, Bisexual, Transgender) patients are neglected worldwide. On the one hand, GPs and medical students in Ireland do not feel prepared to deal with sexual health issues in lesbian, gay and bisexual patients because they do not possess the required communication skills to competently interact with non-heterosexual patients, as shown in a qualitative study by Stott et al [17].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that graduates of residency training programs in psychiatry have had exposure to key issues and considerations for providing quality care to this population, recommendations by Rutherford and colleagues suggest incorporating a mandatory LGBTQ component in the education curriculum [18]. The design of an educational curriculum also needs to be assessed for effectiveness and redesigned as needed.…”
Section: Current Transgender Education Within the Field Of Psychiatrymentioning
confidence: 99%
“…Content examples include a lecture on health disparities among the transgender population, lecture and small group discussions on terminology and interview skills, case presentations, standardized patients who identify as LGBTQ, panel presentations with patients who self-identify with this population, and clinical rotations or electives with a focus in this area [18]. Vance and colleagues administered a transgender youth curriculum to fourth-year medical students, pediatric interns, psychiatry interns, and nurse practitioner students on their 1-month adolescent and young adult medicine rotations [19].…”
Section: Transgender Educational Models In Medical School Curriculumsmentioning
confidence: 99%